عطا شاد ءِ تبکی پگر: Class Consciousness in Poetry of Atta Shad - Rafiq, Sangat; Yousuf, Muhammad (Hanken, 2014)
Atta shad is thought to be the seer of the modern Balochi Poetry, who built up a different form in the Balochi verse. It’s unmistakable that the contemporary Baloch writers presented new styles in advanced Balochi verse, yet Ata Shad is the chief poet, who first time presented the modernistic approach in the Balochi verse. He is the person who utilized a main part of similes, analogies, metaphors and images in his verse. In his verse, he used to let the people know about the class framework, like Karl Marx, in his verses. In this paper, the overwhelming subject ’class framework’ it’s starting point and advancement in the Baloch society will be concentrated.